Bonding in Heavier Group 14 Zero‐Valent Complexes—A Combined Maximum Probability Domain and Valence Bond Theory Approach. Issue 58 (18th September 2017) - Turek, Jan; Braïda, Benoît; De Proft, Frank
Abstract: The bonding in heavier Group 14 zero‐valent complexes of a general formula L2 E (E=Si–Pb; L=phosphine, N ‐heterocyclic and acyclic carbene, cyclic tetrylene and carbon monoxide) is probed by combining valence bond (VB) theory and maximum probability domain (MPD) approaches. All studied complexes are initially evaluated on the basis of the structural parameters and the shape of frontier orbitals revealing a bent structural motif and the presence of two lone pairs at the central E atom. For the VB calculations three resonance structures are suggested, representing the "ylidone", "ylidene" and "bent allene" structures, respectively. The influence of both ligands and central atoms on the bonding situation is clearly expressed in different weights of the resonance structures for the particular complexes. In general, the bonding in the studied E 0 compounds, the tetrylones, is best described as a resonating combination of "ylidone" and "ylidene" structures with a minor contribution of the "bent allene" structure. Moreover, the VB calculations allow for a straightforward assessment of the π‐backbonding (E→L) stabilization energy. The validity of the suggested resonance model is further confirmed by the complementary MPD calculations focusing on the E lone pair region as well as the E–L bonding region. Likewise, the MPD method reveals a strong influence of the σ‐donating and π‐accepting properties of the ligand. In particular, either one single domain or two symmetrical domains are found in the lone pair region of the central atom, supporting the predominance of either the "ylidene" or "ylidone" structures having one or two lone pairs at the central atom, respectively. Furthermore, the calculated average populations in the lone pair MPDs correlate very well with the natural bond orbital (NBO) populations, and can be related to the average number of electrons that is backdonated to the ligands. Abstract : Zero‐valent complexes : Heavier Group 14 zero‐valent complexes, the "tetrylones", are investigated by combining valence bond (VB) theory and maximum probability domain (MPD) approaches. As confirmed by both VB and MPB, the bonding in the studied E 0 (E=Si, Ge, Sn and Pb) compounds is best described as a resonating combination of "ylidone" and "ylidene" structures with a minor contribution of the "bent allene" structure. Moreover, the VB calculations allow for a straightforward assessment of the π‐backbonding stabilization energy.